About expediency of attack and defense parallel study in greco-roman wrestling at the stage of initial training - Kuznetsov, A. S.; Novakovskiy, S. V.; Solomakhin, O. B. (The Russian Journal of Physical Education and Sport, 2018)
As a result of scientific-methodical literature analysis it was revealed that methodical techniques, which help to realize the ideas of gradual skills and abilities mastering, are not developed in Greco-Roman wrestling programs at the stage of initial training. First of all it is necessary to provide standard coordination formation during attacking techniques fulfillment, defensive actions should be considered of secondary importance. If studying technical actions in case of lying fighting, in parterre are fulfilled in terms of relatively stable positions, then in case of standing fighting material mastering happens in terms of non-stable conditions of balance keeping, that is why, there appear serious problems of safety provision in case of cross attacks. In this connection during standing fighting at the initial stage of training it is necessary to provide stable conditions without any outside dynamic interference. At the beginning of teaching throws it is necessary to master medial structure of the technique, the bases of which should be formed in technical actions classification. However, nothing was done for these theses realization in terms of state programs. In some scientific-methodical articles and in the content of the programs conditions for medial structures thorough mastering without distorting factor of outside interference are not taken into consideration. It is offered to study an attacking action simultaneously with defense and counter- techniques against it. Material. In order to reveal expediency of parallel study of attacking and defensive actions natural pedagogical experiment was held. Research methods: scientific-methodical literature analysis and summarizing, pedagogical observation, pedagogical experiment, Greco-Roman style wrestlers` competitive activity study, methods of mathematical statistics. Results. The article presents the analysis of the initial stage programs in Greco-Roman wrestling training. It was revealed that in previous programs methodical techniques, which help to realize the ideas of gradual skills and abilities mastering, were not developed at the stage of initial training in Greco-Roman wrestling. As a result of the pedagogical experiment it was proved that at the end of the 3rd year of study the competitive results of the respondents from the CG and the EF-1 were worse than the results of the EF-2, which didn`t take part in competitions of the 2nd year of study. This fact is connected with the lagged effect of attenuated method of training without defense interference. Conclusion. As a result of a 3-year pedagogical experiment, which included the stage of initial training and the first year of the training stage, it was revealed that it was impractical to study defense and counter-techniques parallel with attacking technical actions during standing fighting.